The Media Fabrication of Georges de Peyrebrune's Networks, a “Little” Naturalist in Blue Stockings - Ménard, Sophie (Thélème. Revista Complutense de Estudios Franceses, 2026)
At a decisive moment in Georges de Peyrebrune's career (1883-1887), this article examines the media strategies by which the author, along with some of her colleagues (Thilda, Delaville, Torrezão), made visible forms of feminine literary sociability. Focusing on the networks Peyrebrune invested in, but also on those she failed to fully integrate, this study examines her exclusion from the Médan circle, her involvement in the “dîner des bas-bleus” and the organization of literary matinees on the Quai d'Orléans, all of which testify to the need for women writers to create alternative spaces of legitimization.
Keywords: Peyrebrune; Zola; cenacle; blue-stockings; networks; press